Catalytic conversion of carbon-containing impurity methyldichlorosilane to purify raw material trichlorosilane of polysilicon production. Issue 7 (11th April 2022) - Geng, Qiang; Huang, Guoqiang
Abstract : Under the condition of activated carbon catalysis, using silicon tetrachloride as the chlorine source, the conversion rate of methyldichlorosilane to methyltrichlorosilane is higher than 80%. Abstract : In order to remove the main carbon impurity methyldichlorosilane from the raw material trichlorosilane used in the production of polysilicon, a catalytic reaction was used to convert it into methyltrichlorosilane with higher boiling point. The catalytic conversion of methyldichlorosilane was carried out by using low-cost materials with different structural properties as catalysts. The three most commonly used low-cost commercial catalysts, A100 resin, activated carbon (AC) and AlCl3, were selected. The physicochemical properties of these low-cost catalysts were characterized by SEM, TEM, BET, XRD and TG technology. The catalytic effects of A100 resin, AC and AlCl3 were compared in a fixed-bed reactor with polysilicon manufacture by-product silicon tetrachloride as the chlorine source. The main focus is to investigate the effects of reaction temperature, molar ratio of reactants, liquid hourly space velocity (LHSV), and catalyst stability on the conversion of methyldichlorosilane. The results show that the AC catalyst had better catalytic effect than AlCl3 and A100 resin catalysts. The optimum process conditions were reaction temperature 140 °C, n (methyldichlorosilane) :  n (silicon tetrachloride) = 1 : 3, and liquid hourly space velocity of 3.0 h −1 . The maximum conversion of methyldichlorosilane is close to 85% under the optimal process conditions. The conversion rate of methyldichlorosilane did not decrease significantly after 120 h, still about 70%, indicating the good catalytic stability of the AC catalyst. Finally, the reaction mechanism of free radical reaction is well explained.